Are we using oxycodone appropriately? A utilisation review in a UK tertiary care centre. Issue 2 (30th October 2012) - Todd, A; Husband, A; Richardson, R; Jassal, N; Robson, P; Andrew, I
Abstract : Objectives: To evaluate the utilisation of oxycodone in a tertiary care centre based in the North of England serving a population of 330 000. Methods: A prospective study which gathered data from October 2011 to March 2012. Medical notes were screened to determine the prevalence of oxycodone use during the study period. The medication histories were determined; once the reason for oxycodone initiation was established, it was interpreted and classified as either appropriate or inappropriate. Results: During the study period, a total of 51 patients were taking oxycodone; one patient was lost to follow-up. General practitioners were found to be the most common group responsible for initiating oxycodone (22 patients, 44%), followed by specialist palliative care nurses (11 patients, 22%). Other prescribers included palliative care consultants (nine patients, 18%); hospital doctors (seven patients, 14%) and a site-specific specialist nurse (one patient, 2%). Of the 50 patients, 17 (34%) were considered to be using oxycodone inappropriately. The most frequent reason for inappropriate use was initiating oxycodone without initially trying morphine. Conclusions: Oxycodone is initiated inappropriately in a significant number of palliative care patients and should only be used as a second-line strong opioid or if morphine is not suitable or cannot be tolerated. The specialist palliative care team should be consulted for advice in cases of complex pain management.